(untitled) (Research, Society and Development, 2022)
Introduction: The term patient safety refers to the reduction of unnecessary risks and harm associated with health care or to an acceptable minimum in health care. Aiming at this, the National Program for Patient Safety was instituted, taking its specific objectives to the need to build, systematize and disseminate knowledge on the subject. In view of this, it is known that the organization and communication among health professionals are essential to avoid adverse events, these being the biggest challenges to maintain patient safety. Methodology: The databases Virtual Health Library (BVS) and Scientific Electronic Library Online (SciELO) were used to search for articles, as well as Google for the necessary legislation related to the content in question. The inclusion criteria for the studies were scientific research available online in full text in article format, published within the timeframe, in Portuguese and English, and excluded articles not related to the proposed theme and studies with a methodological design that did not allow the identification of the proposed objective. Conclusion: Patient safety is a primordial process so that the assistance offered is safe and effective in all areas of health. Although it is extremely important, many are the obstacles related to the application in practice of patient safety, such as the lack of human resources in sufficient quantity and quality. The healthcare institution must promote the improvement of these professionals so that they can be adequately trained.